Sacred precincts : the religious architecture of non-Muslim communities across the Islamic world - Gharipour, Mohammad; Guidetti, Mattia. (Arts and Archaeology of the Islamic World, 2014)
This book examines non-Muslim religious sites, structures and spaces in the Islamic world. It reveals a vibrant portrait of life in the religious sites by illustrating how architecture responds to contextual issues and traditions. Sacred Precincts explores urban context; issues of identity; design; construction; transformation and the history of sacred sites and architecture in Europe, the Middle East and Africa from the advent of Islam to the 20th century. It includes case studies on churches and synagogues in Iran, Turkey, Cyprus, Egypt, Iraq, Tunisia, Morocco and Malta, and on sacred sites in Nigeria, Mali, and the Gambia. With contributions by Clara Alvarez, Angela Andersen, Karen Britt, Karla Britton, Jorge Manuel Simão Alves Correia, Elvan Cobb, Daniel Coslett, Mohammad Gharipour, Mattia Guidetti, Suna Güven, Esther Kühn, Amy Landau, Ayla Lepine, Theo Maarten van Lint, David Mallia, Erin Maglaque, Susan Miller, A.A. Muhammad-Oumar, Meltem Özkan Altınöz, Jennifer Pruitt, Rafael Sedighpour, Ann Shafer, Jorge Manuel Simão Alves Correia, Ebru Özeke Tökmeci, Steven Thomson, Heghnar Watenpaugh, Alyson Wharton and Ethel S. Wolper.